Fat-soluble vitamin and phytochemical metabolites: Production, gastrointestinal absorption, and health effects. (April 2023) - Borel, Patrick; Dangles, Olivier; Kopec, Rachel E.
Abstract: Consumption of diets rich in fruits and vegetables, which provide some fat-soluble vitamins and many phytochemicals, is associated with a lower risk of developing certain degenerative diseases. It is well accepted that not only the parent compounds, but also their derivatives formed upon enzymatic or nonenzymatic transformations, can produce protective biological effects. These derivatives can be formed during food storage, processing, or cooking. They can also be formed in the lumen of the upper digestive tract during digestion, or via metabolism by microbiota in the colon. This review compiles the known metabolites of fat-soluble vitamins and fat-soluble phytochemicals (FSV and FSP) that have been identified in food and in the human digestive tract, or could potentially be present based on the known reactivity of the parent compounds in normal or pathological conditions, or following surgical interventions of the digestive tract or consumption of xenobiotics known to impair lipid absorption. It also covers the very limited data available on the bioavailability (absorption, intestinal mucosa metabolism) and summarizes their effects on health. Notably, despite great interest in identifying bioactive derivatives of FSV and FSP, studying their absorption, and probing their putative health effects, much research remains to be conducted to understand and capitalize on the potential of these molecules to preserve health. Highlights: Some derivatives of fat-soluble vitamins and phytochemicals have biological effects. They can be formed upon enzymatic modifications or physicochemical degradations. They can be formed in food, the upper digestive tract lumen or via the microbiota. Some diseases of the gastrointestinal tract affect the production of derivatives. Some lipid absorption inhibitors affect the production of some of the derivatives.